From Logical Positivism to a Poetics of the Ineffable: The Place of Ingeborg Bachmann’s Texts in the History of Readings of the Tractatus Logico-Philosophicus - Decauwert, Guillaume (Scenari, 2022)
The Austrian poet and novelist Ingeborg Bachmann, also a Doctor of Philosophy, has devoted to Wittgenstein several theoretical writings which could indicate a significant moment in the German-speaking reception of the Tractatus. These texts have helped to open the way to a reading of the Tractatus that aims to interpret the work without separating its logical content from its poetic force, i.e. to articulate Wittgenstein’s demand for intellectual clarity and his call for silence before the ineffable. Her writings of the 1950s on the Tractatus take Wittgenstein’s concluding remarks seriously without leaving aside his complex logical path and indicate the importance of his distinction between the sayable and the unsayable. In this paper, I want to show that I. Bachmann manages to give meaning to the original and paradoxical approach of the author of the Tractatus thanks to her knowledge of the complex relationship between fin-de-siècle Vienna and modern rationalism, and of the struggle of the Wiener Kreis against speculative metaphysics, as well as a philosophical culture and a strong poetic sensitivity that allow her to identify the spiritual significance of a “positive silence” brought about by the “negative›› philosophy” that she recognizes in Wittgenstein’s reflection on the limits of language.